Fostering Environmental Awareness Through Sustainable Development Goal-Oriented Ethno-STEM Approach in Elementary Education - Pada, Amir; Chanunan, Skonchai; Rahmat, Irwandi (Jurnal Pendidikan IPA Indonesia, 2025)
This study examines the effectiveness of a Sustainable Development Goals (SDGs)-oriented Ethno-STEM approach in promoting environmental awareness among elementary school students through natural and social science learning. Utilizing a quasi-experimental one-group pretest-posttest design, the research involved 60 students from an elementary school in Makassar, Indonesia. Environmental awareness was assessed before and after the implementation of Ethno-STEM-integrated lessons that incorporated culturally relevant and participatory activities such as eco-brick making, waste management simulations, and the "Zero Plastic Week" challenge. Data were analyzed using a paired t-test, which revealed a statistically significant improvement in students' environmental awareness scores (p = 0.001), with the mean increasing from M = 61.06 (SD = 7.10) to M = 68.61 (SD = 6.63). The findings demonstrate that integrating local cultural values and sustainability themes into science education fosters both cognitive understanding and behavioral engagement with environmental issues. This study contributes to the development of culturally contextualized and sustainability-focused pedagogy, reinforcing the relevance of SDG 4 (quality education) and SDG 13 (climate action). This study is novel in its integration of SDGs-oriented Ethno-STEM with elementary science education, demonstrating not only cognitive improvement but also fostering affective and behavioral engagement. Its contribution lies in bridging cultural relevance with sustainability pedagogy, thereby informing both theoretical discourse and practical applications in early education.